(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Palliative care (PC) is increasingly recognized as an essential component of highquality cancer care, with evidence from randomized trials and meta-analyses demonstrating that it improves quality of life, mood, and goal-concordant end-of-life care. Despite these benefits, PC integration has been inconsistent, with many patients still receiving PC later in their disease course. Current models of integration include outpatient colocated PC clinics, inpatient consultation services, community and home-based programs, and more recent innovations, such as telehealth and stepped approaches. These models have shown clear benefits; however, they are frequently organized by care settings rather than patient-specific needs, resulting in both underuse and inefficiency. Emerging evidence has begun to clarify the mechanisms through which PC provides patient benefits. Symptom control, coping support, longitudinal communication, and existential or spiritual interventions are among the active ingredients that are most consistently associated with improvements in patient outcomes. Recognition of these mechanistic drivers highlights the potential for precision PC, in which care is tailored to the unique drivers of each patient’s needs. Implementation of precision PC requires embedding validated patient-reported outcomes and structured referral algorithms into oncology workflows, enabling real-time triage of targeted interventions. Interoperable technology, workforce expansion through the training of non-specialists, and policy reforms that support scalable delivery models, such as telehealth and nurse-led pro- grams, will be essential for closing gaps in terms of access and equity. Precision PC offers a pragmatic framework for aligning limited resources with the diverse and evolving needs of patients with cancer, ensuring timely, individualized, and sustainable integration into modern oncology.